Kinetics of Nanomedicine in Tumor Spheroid as an In Vitro Model System for Efficient Tumor-Targeted Drug Delivery With Insights From Mathematical Models - Roy, Sayoni Maitra; Garg, Vrinda; Barman, Sourav; Ghosh, Chitrita; Maity, Amit Ranjan; Ghosh, Surya K. (Frontiers in Bioengineering and Biotechnology, 2021)
Numerous strategies have been developed to treat cancer conventionally using the chemotherapeutic method. Nonetheless, the complex behavior of the tumor microenvironment frequently impedes successful drug delivery to the tumor sites that further demands very urgent and effective distribution of anticancer drugs specifically to the sites. Hence targeted drug delivery to tumor sites has become a major challenge for cancer therapy by assuring drug effects to selectively tumor tissue and overcoming undesired toxic side effects to the normal tissues. Aiming to limit the use of traditional strategies, the adequacy of nanomedicine proves worthwhile. Understanding the potential tumor targeting barriers and limiting conditions for nanomedicine extravasation, tumor penetration, and final accumulation of the anticancer drug to tumor mass; experiments with in vivo animal models, for screening of nanomedicine, is a key step before it reaches clinical translation. Although the study with animals is undoubtedly valuable, it has many associated ethical issues. Moreover, individual experiments are very expensive and take a longer time to conclude. To cinch these issues, multicellular tumor spheroids are considered as promising in vitro model that proposes better replication of in vivo tumor properties for the future development of new therapeutics. In this review, we will discuss how tumor spheroids could be used as an in vitro model system to screen nanomedicine used in targeted drug delivery aiming to better therapeutic benefits. In addition, the recent proliferation of mathematical modeling approaches gives profound insight into the underlying physical principles and produces quantitative predictions. To study targeted drug delivery, mathematical modeling of tumor architecture, its growth, the concentration gradient of oxygen are the points of prime focus. Quantitative models are not only circumscribed to the spheroid but also the role of modeling for the nanoparticle is equally inevitable. Thus, to diffuse the dichotomy among the chemistry involved, biological data, and the underlying physics, the mathematical models play an indispensable part that can assist the experimentalist for further evaluation by providing the admissible quantitative approach which can be validated. This review will provide an overview of the targeted drug delivery mechanism for spheroid, using nanomedicine as an advantageous tool.